A dog’s wisdom : - Bonham, Margaret H. (Howell Book House, 2005)
Live spontaneously. Be who you are. Hang tough. Be curious. Take a siesta. Through a collection of delightful vignettes, author and dog-lover extraordinaire Maggie Bonham shares the lessons she's learned from beloved dogs. Dogs live in the moment, forgetting yesterday's slights and not worrying about tomorrow's plight, but finding joy and contentment wherever they can. Following their instinctive lead can enrich your philosophies on home, work, play, friends, love, relationships, raising a family, life, health, and more. Complete with tips from canines Kodiak, Kira, Ranger, and Haegl, A Dog's Wisdom is a stirring celebration of the special bond between people and the dogs they love. Through compelling stories and touching photographs, A Dog's Wisdom will inspire you to look at the world with renewed enthusiasm and wonder--and to look at your best friends even more appreciatively and affectionately.